Effect of Dementia, Family Support, Peer Support, Type of Residence, and Marital Status on Quality of Life of the Elderly in Surakarta, Central Java - Sri Suwarni; RB. Soemanto; Aris Sudiyanto (Journal of Epidemiology and Public Health, 2018)
Background: The aging population is increasing in Indonesia and worldwide. Indonesia is one of the countries that has high aging population structure. As such, the quality of life of the elderly is of major concern. This study aimed to determine the effect of dementia, family support, peer support, type of residence, and marital status on quality of life of the elderly in Surakarta, Central Java.Subjects and Method: This was an analytical observational study with cross-sectional design.  A total sample of 218 elderly people in Surakarta, Central Java, was selected for this study by fixed exposure sampling, with 1:3 ratio consisting of 50 elderly people living in Dharma Bakti nursing home and 168 elderly people living with their families in the community. The dependent variable was health-related quality of life. The independent variables were dementia, family support, peer support, type of residence, and marital status. The data were collected by questionnaire and analyzed by path analysis.Results: Better quality of life of the elderly was directly increased by strong peer support (b= 0.25, p<0.001), strong family support (b= 0.59, p= 0.002), mild dementia (b= 1.79, p<0.001), and being married (b= 12.73, p= 0.039). Better quality of life was also increased indirectly by strong peer support (b= 0.67, p= 0.012) and living with families (b= 22.93, p<0.001), through family support.Conclusion: Better quality of life of the elderly is directly increased by strong peer support, strong family support, mild dementia, and being married. It is indirectly increase by strong peer support and living with families.Keyword: quality of life, dementia, family support, peer support, elderlyCorrespondence: Sri Suwarni. School of Health Polytechnics, Ministry of Health, Surakarta. Email: tanasfa@gmail.comJournal of Epidemiologi and Public Health (2018), 3(1): 83-94https://doi.org/10.26911/jepublichealth.2018.03.01.07